Cover Picture: A Strategy to Control the Reactivation of Frustrated Lewis Pairs from Shelf‐Stable Carbene Borane Complexes (Angew. Chem. Int. Ed. 40/2015). Issue 40 (24th August 2015) - Hoshimoto, Yoichi; Kinoshita, Takuya; Ohashi, Masato; Ogoshi, Sensuke
<x xml:space="preserve">Abstract</x> A magician is looking into his crystal ball to read the future of a Lewis acid–base adduct. When his hand (an external stimulus) catches and rotates the phosphine oxide moiety, a highly active frustrated Lewis pair is formed in a process that is studied by S. Ogoshi, Y. Hoshimoto et al. in their Communication on page 11666 ff. This reactivation of frustration (and the high reactivity) is shown as a cracking of the crystal ball.